MULTIPLICIDADE DE VOZES: QUATRO PROPOSTAS DE LEITURA DE “CASA TOMADA”, DE CORTÁZAR - Silva Santos, Marinna; Andrea Rodrigues Benfatti, Flávia (Revista de Letras, 2024)
This article aims to analyse the short story "Casa Tomada" (1946), by Julio Cortázar, from the perspective of Fred Botting's gothic literary theory, with contributions from Barthes' structuralism, Rancière's political aesthetics and Jauss' reception studies. Based on Botting (2005) we adopt the argument that elements such as values transgression and defiance towards traditional institutions suggests that Cortázar intentionally employed gothic aesthetics as a literary resource, and therefore "Casa Tomada" can be considered a gothic tale. We also counterpose the perspectives from Barthes (2011) and Rancière (2005), in regards to structural analysis of narrative and the expression of sociopolitical conflict in the Argentina of Cortázar's time. Jauss' (1994) theory is used in order to examine the reader's horizon of expectations and its importance in the reception and interpretation of a written work. In such a sense, to look at the short story's reception means not to neglect the context of its production.